DAMPAK SUBSIDI PUPUK TERHADAP KESEJAHTERAAN PETANI DAN DAYA SAING KOMODITAS TANAMAN PANGAN PADI JAGUNG KEDELAI - Dahiri; Adhi Prasetyo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2018)
This research purpose to look at the impact of fertilizer subsidy subsidies on farmers' welfare and the competitiveness of commodity crops for paddy, corn and soybeans. The study used Policy Analysis Matrix (PAM) Agriculture to assess the impact of price policies and investment policies. Based on these findings the fertilizer subsidies are able to improve the welfare of farmers and create competitiveness of food crops in rice, corn and soybeans. It is hoped that the government will be able to improve the management of fertilizer subsidies since the fertilizer subsidies has not been fully impacted by rice, corn and soybean farmers.